DYSCIRCULATORY ENCEPHALOPATHY ON THE BACKGROUND OF HYPOTHYROIDISM - Mamurova Malika Mirkhamzaevna; Emrah Kelesh Ismetovich (Scholar Express Journals, 2022)
Chronic insufficiency of cerebral circulation, or discirculatory encephalopathy, is a widespread group of cerebral vascular diseases (detected in 20 - 30% of persons of working age and tends to increase in the structure of vascular diseases of the nervous system). This pathology is based on multifocal or diffuse lesions of the brain, manifested clinically by neurological, neuropsychological and/or mental disorders caused by chronic cerebral vascular insufficiency and/or repeated episodes of acute violations of cerebral circulation. Cognitive impairment is one of the main clinical manifestations of chronic cerebral circulatory insufficiency.
Keywords: Thyroid Hormones; Lipid Status; Clinical Hypothyroidism; Subclinical Hypothyroidism